A puzzle about meaning and luck - HAMMERTON, Matthew (Institutional Knowledge at Singapore Management University, 2022)
This article raises a puzzle about luck and meaning in life. The puzzle shows that, in certain cases involving luck, standard intuitions about the meaningfulness of various lives conflict with basic theoretical assumptions about the nature of meaning. After setting out the puzzle, several options for resolving it are developed and evaluated.